Organic solvent-water double-solvent composite hydrogel as well as preparation method and application thereof
By synthesizing organic silicone enhanced polyvinyl alcohol composite hydrogel and preparing organic solvent-water double solvent composite hydrogel through solvent replacement, the balance problem of polymer hydrogel between mechanical strength and electrical conductivity is solved, and the balance problem of polymer hydrogels is achieved. High sensitivity detection of strain, suitable for wearable strain sensors.
Patent Information
- Application Number
- CN202411371617.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-29
AI Technical Summary
As wearable strain sensors, existing polymer hydrogels are difficult to meet the needs of mechanical strength and conductivity at the same time, and are prone to dehydration in low-humidity environments and easily swelling in high-humidity environments, which limits their application scenarios.
The polyvinyl alcohol composite hydrogel is enhanced by synthesis of silicone, and the organic solvent-water double solvent composite hydrogel is prepared through solvent replacement strategy to improve its mechanical properties, water retention and electrical properties.
The obtained organic solvent-water double solvent composite hydrogel has good cycle stability and extremely high sensitivity, and can detect extremely small strain signals in real time. It is suitable for monitoring large human movements and facial micro-expression changes.
Smart Images

Figure CN119219943A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogel and flexible sensing, and in particular relates to an organic solvent-water double solvent composite hydrogel and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Flexible, extendable, wearable strain sensors that can simultaneously detect external deformation in real time and convert it into electrical signals have attracted extensive attention due to their important roles in electronic skin, soft robotics, human-machine interfaces, and human health monitoring. Strain sensors exhibit changes in elongation and shortening under external forces to generate reproducible electrical signals. However, most strain sensors have limitations such as narrow detection range, small tensile strain, poor durability, and cumbersome preparation methods.
[0004] Polymer hydrogel is a three-dimensional cross-linked network gel formed by physical or chemical cross-linking with water as the dispersion medium. It has the characteristics of simple synthesis process and easy adjustment of water content. It can maintain structural integrity during deformation and has flexibility similar to biological tissue. Compared with traditional strain sensor materials such as metals and polymers, hydrogels have better mechanical properties, but the defects of hydrogels such as easy dehydration in low humidity environments and easy swelling in high humidity environments or water environments inhibit their mechanical strength and function, limiting the application scenarios of hydrogels as strain sensors. In addition, although the introduction of conductive fillers such as MXenes, carbon nanotubes, rGO, graphene, polypyrrole and polyaniline into the hydrogel matrix can improve the conductivity of hydrogels, the introduction of fillers affects the mechanical properties and mechanical strength of the hydrogels themselves. It is still difficult for polymer hydrogels to meet the needs of mechanical strength and conductivity at the same time as wearable strain sensors. Summary of the invention
[0005] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide an organic solvent-water dual solvent composite hydrogel and its preparation method and application. The present invention first synthesizes and prepares a tough and conductive organosilicon-reinforced polyvinyl alcohol composite hydrogel, and further prepares an organic solvent-water dual solvent composite hydrogel with significantly enhanced mechanical properties, water retention properties and electrical properties through a solvent replacement strategy, which can be used as a wearable strain sensor to detect extremely small strains, including smiling and talking.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing an organic solvent-water dual solvent composite hydrogel, comprising the following steps:
[0008] S1, dissolving aminopolysilane and polyvinyl alcohol in water and heating for reaction, adding polyacid for reaction to obtain a mixture, and centrifuging, freezing and thawing the mixture to obtain a silicone-reinforced polyvinyl alcohol composite hydrogel;
[0009] S2. placing the organosilicon-reinforced polyvinyl alcohol composite hydrogel in an organic solvent or an aqueous solution of an organic solvent for solvent replacement to obtain an organic solvent-water dual solvent composite hydrogel.
[0010] Preferably, in step S1, the aminopolysilane is prepared by mixing aminosilane and water, heating to reflux, removing water in vacuo, and cooling under reduced pressure.
[0011] Further preferably, the aminosilane includes at least one of 3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, N-(β-aminoethyl-γ-aminopropyl)methyldiethoxysilane and trimethoxy[3-(methylamino)propyl]silane, and the molar ratio of the aminosilane to water is 1:(2 to 5).
[0012] More preferably, the mixture is heated to 140°C to 160°C in a N2 atmosphere and refluxed for 1 to 2 hours, and water is removed in vacuo at 140°C to 160°C for 1 to 2 hours, and then cooled to 20°C to 30°C under reduced pressure.
[0013] Preferably, in step S1, the mass ratio of aminopolysilane to polyvinyl alcohol is (0.0625-0.75):1, the polyacid includes at least one of phytic acid, citric acid and tripolyphosphoric acid, and the ratio of polyvinyl alcohol, water and polyacid is (1g):(5-7mL):(3-5mL).
[0014] Preferably, in step S1, the mixture is heated to 90°C to 100°C for reaction for 1 to 2 hours, and a polyacid is added for reaction for 1 to 2 hours.
[0015] Preferably, in step S2, the organic solvent includes at least one of ethanol, propylene glycol and dimethyl sulfoxide, and the volume concentration of the organic solvent in the aqueous solution of the organic solvent is 0% to 100% and does not include 0% and 100%; the time for solvent replacement is 12 to 48 hours, and the number of solvent replacements is 1 to 3 times.
[0016] In a second aspect, the present invention provides an organic solvent-water dual solvent composite hydrogel obtained by the preparation method described in the first aspect.
[0017] In a third aspect, the present invention provides an application of the organic solvent-water dual solvent composite hydrogel as described in the second aspect in flexible sensing.
[0018] In a fourth aspect, the present invention provides a wearable strain sensor comprising the organic solvent-water dual solvent composite hydrogel as described in the second aspect.
[0019] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:
[0020] Aminopolysilane was introduced into the polyvinyl alcohol matrix, and silicone-reinforced polyvinyl alcohol composite hydrogel was obtained by crosslinking with polyacids and freeze-thaw cycles. Polyvinyl alcohol was crosslinked to form a main network through freeze-thaw cycles, and polyacid-crosslinked aminopolysilane was used as a second network. The two networks were interspersed and connected by polyacids. Organic solvent-water dual solvent composite hydrogel was further obtained by solvent replacement, and the mechanical properties, water retention properties and electrical properties of the composite hydrogel were improved by regulating the type and concentration of the organic solvent.
[0021] The organic solvent-water dual-solvent composite hydrogel responds quickly to different strains, has good cyclic stability, shows very high repetitive response ability and extremely high sensitivity, can detect extremely small strain signals in real time, and the waveforms obtained are basically the same.
[0022] Organic solvent-water dual solvent composite hydrogel can effectively monitor large-scale human body movements (large deformation) and facial micro-expression changes (small deformation). The signal detection is sensitive and stable, and it can be used as a wearable strain sensor material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0024] Figure 1 (a) Photos of PVA / PA / APSi hydrogels immersed in different organic solvents, (b) Comparison of the morphology of the organic solvent-water dual solvent composite hydrogels of Examples 1 to 6 and the PVA / PA / APSi hydrogel of Comparative Example 1, (c) Comparison of the volume and mass of the PVA / PA / APSi hydrogels in Comparative Example 1, Example 1, Example 2 and Comparative Example 1 after water replacement, (d) Comparison of the volume and mass of the PVA / PA / APSi hydrogels in Comparative Example 1, Example 3, Example 4 and Comparative Example 1 after water replacement, (e) Comparison of the volume and mass of the PVA / PA / APSi hydrogels in Comparative Example 1, Example 5, Example 6 and Comparative Example 1 after water replacement;
[0025] Figure 2The stress-strain curves of the organic solvent-water dual solvent composite hydrogels of Examples 1 to 6 and the PVA / PA / APSi hydrogel of Comparative Example 1;
[0026] Figure 3 The loading-unloading cycle curves of the organic solvent-water dual solvent composite hydrogels of Examples 1 to 6 under different strains;
[0027] Figure 4 The photos are of the organic solvent-water dual solvent composite hydrogels of Examples 1 to 6 and the PVA / PA / APSi hydrogel of Comparative Example 1 at different times at room temperature;
[0028] Figure 5 (a) The state of the Gly (50%) hydrogel of Example 3 at -50°C, (b) DCS curves of the hydrogels of Comparative Example 1, Example 3, and Example 4;
[0029] Figure 6 The linear relationship between (a) conductivity and (b) relative resistance change and strain of the organic solvent-water dual solvent composite hydrogels of Examples 1 to 6 and the PVA / PA / APSi hydrogel of Comparative Example 1;
[0030] Figure 7 The relative resistance change and stability of the Gly (50%) hydrogel in Example 7 under large strain (fingers, joints) and small strain (speaking, smiling). DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0032] Example 1
[0033] N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane (AEAPMDS, 105.3 g, 0.5 mol) and water (21.6 g, 1.2 mol) were mixed in a 500 mL three-necked flask and refluxed at 150° C. for 1 hour under N2 atmosphere. Then the mixture was kept at 150° C. under vacuum for 1 hour to remove byproducts of methanol and water and further promote the condensation of siloxane molecules. Finally, the product was cooled to 25° C. under reduced pressure to obtain a clear viscous liquid aminopolysiloxane APSi (yield: 94%).
[0034] PVA (5.0 g) and APSi (1.875 g) were dissolved in deionized water (30 mL) in a 250 mL three-necked flask and stirred in an oil bath at 95 ° C for 1 h until the solution became clear. PA (20 mL) was continued to be added and stirred for 1 h until a clear mixture was obtained. The mixture was centrifuged at 4000 rpm for 10 minutes to remove bubbles and then poured into a mold. The mold was frozen at -20 ° C for 21 h and thawed at room temperature for 3 h. After repeating this process three times, a silicone-enhanced polyvinyl alcohol composite hydrogel (PVA / PA / APSi hydrogel) was obtained. Finally, the obtained PVA / PA / APSi hydrogel was soaked in distilled water for 24 hours and replaced three times to remove any residue.
[0035] like Figure 1 As shown in (a), the PVA / PA / APSi hydrogel was immersed in a 50% volume concentration ethanol (EtOH) aqueous solution for 12 hours to obtain an organic solvent-water dual solvent composite hydrogel, which was recorded as EtOH (50%) hydrogel.
[0036] Example 2
[0037] The preparation of aminopolysiloxane APSi is the same as in Example 1.
[0038] The preparation of PVA / PA / APSi hydrogel is the same as in Example 1.
[0039] like Figure 1 As shown in (a), the PVA / PA / APSi hydrogel was immersed in 100% ethanol for 12 hours to obtain an organic solvent-water dual solvent composite hydrogel, which was recorded as EtOH (100%) hydrogel.
[0040] Example 3
[0041] The preparation of aminopolysiloxane APSi is the same as in Example 1.
[0042] The preparation of PVA / PA / APSi hydrogel is the same as in Example 1.
[0043] like Figure 1 As shown in (a), the PVA / PA / APSi hydrogel was immersed in a 50% volume concentration of glycerol (Gly) aqueous solution for 12 hours to obtain an organic solvent-water dual solvent composite hydrogel, which was recorded as Gly (50%) hydrogel.
[0044] Example 4
[0045] The preparation of aminopolysiloxane APSi is the same as in Example 1.
[0046] The preparation of PVA / PA / APSi hydrogel is the same as in Example 1.
[0047] like Figure 1 As shown in (a), the PVA / PA / APSi hydrogel was immersed in 100% propylene glycol for 12 hours to obtain an organic solvent-water dual solvent composite hydrogel, which was recorded as Gly (100%) hydrogel.
[0048] Example 5
[0049] The preparation of aminopolysiloxane APSi is the same as in Example 1.
[0050] The preparation of PVA / PA / APSi hydrogel is the same as in Example 1.
[0051] like Figure 1 As shown in (a), the PVA / PA / APSi hydrogel was immersed in a 50% volume concentration dimethyl sulfoxide (DMSO) aqueous solution for 24 hours and replaced three times to obtain an organic solvent-water dual solvent composite hydrogel, recorded as DMSO (50%) hydrogel.
[0052] Example 6
[0053] The preparation of aminopolysiloxane APSi is the same as in Example 1.
[0054] The preparation of PVA / PA / APSi hydrogel is the same as in Example 1.
[0055] like Figure 1 As shown in (a), the PVA / PA / APSi hydrogel was immersed in 100% dimethyl sulfoxide for 12 hours to obtain an organic solvent-water dual solvent composite hydrogel, which was recorded as DMSO (100%) hydrogel.
[0056] Comparative Example 1
[0057] PVA / PA / APSi hydrogel was synthesized with reference to Example 1 for comparison.
[0058] like Figure 1 As shown, after the hydrogel was immersed in 50% EtOH solution and Gly solution for solvent replacement, it was found that its mass and volume were significantly reduced. After being immersed in 100% EtOH and Gly for full replacement, its mass and volume were reduced to about 40% of the original. This is because the molecular structure of the hydrogel is less compatible with EtOH and Gly than water. When the hydrogel was immersed in 50% DMSO solution for full replacement, the mass and volume of the hydrogel were significantly reduced. When immersed in 100% DMSO, the mass and volume of the hydrogel increased to about 250% of the original, which may be because the molecular structure of the hydrogel is more compatible with DMSO than water.
[0059] like Figure 2As shown in Table 1, the tensile strength of the hydrogels significantly increased after solvent replacement in EtOH and Gly. The tensile strength increased after solvent replacement in 50% DMSO, while the tensile strength decreased after solvent replacement in 100% DMSO. The change in the tensile strength of the hydrogels was consistent with the mass and volume changes after solvent replacement, which indicates that the changes in the mechanical properties of the hydrogels were caused by mass and volume changes.
[0060] Table 1 Tensile strength and elongation at break of hydrogels in Examples 1 to 6 and Comparative Example 1
[0061]
[0062] like Figure 3 As shown in the figure, the hysteresis loop of the hydrogel increases after solvent replacement, and the energy dissipation efficiency is improved. This may be because the intermolecular interaction between these three organic solvents and water is stronger than that between water and water, and more energy is consumed when the force is loaded. This also affects the mechanical properties of the hydrogel to a certain extent.
[0063] Hydrogels contain abundant free water and always suffer from severe dehydration, which greatly hinders their practical application scenarios and further commercialization. Figure 4 The following are photos of the dehydration of the hydrogels in Examples 1 to 6 and Comparative Example 1 at room temperature. It can be seen that the PVA / PA / APSi hydrogel in Comparative Example 1 completely lost water in 36 hours. The EtOH-replaced hydrogels in Examples 1 and 2 lost water faster due to the strong volatility of EtOH. The DMSO-replaced hydrogels in Examples 5 and 6 lost water more slowly. The Gly (50%) hydrogel in Example 5 showed good water retention due to the water-locking effect of Gly, and there was no obvious change in its morphology after being placed at room temperature for 168 hours. This is because Gly is relatively non-volatile and forms dense hydrogen bonds with water molecules to prevent the evaporation of water. In addition, the presence of hydrogen bonds also inhibits the formation of ice crystals, making the Gly (50%) hydrogel still soft at -50°C (such as Figure 5 From the DSC spectrum ( Figure 5 As can be seen from (b)), with the increase of Gly content, the freezing point of Gly hydrogel gradually decreases from -12.3℃ to below -120℃, which means that Gly hydrogel can be used at low temperatures. Therefore, the introduction of Gly gives hydrogel both antifreeze and heat resistance properties. The solvent replacement strategy is an effective means to improve the stability and applicability of hydrogels in various environments by replacing part of the water with organic molecules.
[0064] The electrical properties (conductivity, sensitivity coefficient, linear coefficient) of the organic solvent-water dual solvent composite hydrogel also changed significantly. Figure 6As shown in (a), since the hydrogel is ion conductive, H + It mainly comes from the ionization of PA. In the mixed solvent, the degree of PA ionization is reduced, and the volume shrinkage of the hydrogel in the mixed solvent leads to a reduction in pore size, which is not conducive to the free shuttle of H+, so the conductivity of the hydrogel is reduced. Figure 6 As shown in (b), the hydrogel has a uniform network structure, so the resistance change of all organic solvent-water dual solvent composite hydrogels shows an obvious linear relationship with strain. As far as use as wearable strain sensors is concerned, the sensitivity factor (GF) is a relatively more important factor in electrical properties. As shown in Table 2, the GF of the Gly (50%) hydrogel of Example 3, the DMSO (50%) hydrogel of Example 5, and the DMSO (100%) hydrogel of Example 6 are much higher than that of the PVA / PA / APSi hydrogel, and the GF of the EtOH (50%) hydrogel of Example 2 is also higher than that of the PVA / PA / APSi hydrogel.
[0065] Table 2 Conductivity and GF of hydrogels in Examples 1 to 6 and Comparative Example 1, and linear fitting equations of relative resistance change and hydrogel strain
[0066]
[0067] Example 7
[0068] The Gly (50%) hydrogel of Example 3 was connected to a wire as a wearable strain sensor and attached to fingers, wrists, knee joints, face and neck to test its cyclic stability under different strain conditions. Figure 7 As shown, Gly (50%) hydrogel responds quickly to different strains, has good cyclic stability, and shows very high repetitive response ability and extremely high sensitivity. Moreover, Gly (50%) hydrogel has a higher GF and can detect extremely small strain signals in real time, including smiling and talking, and the waveforms obtained are basically the same. Gly (50%) hydrogel can be used as a wearable strain sensor to effectively monitor large-scale human movements (large deformations) and facial micro-expression changes (small deformations), and the signal detection is sensitive and stable.
[0069] Example 8
[0070] Different from Example 3, PVA (5.0 g) and APSi (0.3125 g) were dissolved in deionized water (30 mL) in a 250 mL three-necked flask.
[0071] Example 9
[0072] Different from Example 3, PVA (5.0 g) and APSi (0.625 g) were dissolved in deionized water (30 mL) in a 250 mL three-necked flask.
[0073] Example 10
[0074] Different from Example 3, PVA (5.0 g) and APSi (1.25 g) were dissolved in deionized water (30 mL) in a 250 mL three-necked flask.
[0075] Embodiment 11
[0076] Different from Example 3, PVA (5.0 g) and APSi (1.875 g) were dissolved in deionized water (30 mL) in a 250 mL three-necked flask.
[0077] Example 12
[0078] Different from Example 3, PVA (5.0 g) and APSi (2.5 g) were dissolved in deionized water (30 mL) in a 250 mL three-necked flask.
[0079] Example 13
[0080] Different from Example 3, PVA (5.0 g) and APSi (3.75 g) were dissolved in deionized water (30 mL) in a 250 mL three-necked flask.
[0081] Embodiment 14
[0082] 3-Aminopropyldimethylmethoxysilane (73.7 g, 0.5 mol) and water (21.6 g, 1.2 mol) were mixed in a 500 mL three-necked flask and refluxed at 150° C. for 1 hour under N2 atmosphere. Then, the mixture was kept at 150° C. under vacuum for 1 hour to remove byproducts of methanol and water and further promote the condensation of siloxane molecules. Finally, the product was cooled to 25° C. under reduced pressure to obtain a clear viscous liquid aminopolysilane.
[0083] PVA (5.0 g) and aminopolysilane (1.875 g) were dissolved in deionized water (30 mL) in a 250 mL three-necked flask and stirred in an oil bath at 95 ° C for 1 h until the solution became clear. Continue to add PA (20 mL) and stir for 1 h until a clear mixture is obtained. The mixture was centrifuged at 4000 rpm for 10 minutes to remove bubbles and then poured into a mold. The mold was frozen at -20 ° C for 21 h and thawed at room temperature for 3 h. After repeating this process three times, a silicone-enhanced polyvinyl alcohol composite hydrogel was obtained. Finally, the obtained silicone-enhanced polyvinyl alcohol composite hydrogel was soaked in distilled water for 24 hours and replaced three times to remove any residues.
[0084] The organosilicon reinforced polyvinyl alcohol composite hydrogel was immersed in a 50% volume concentration glycerol (Gly) aqueous solution for 12 hours to obtain an organic solvent-water dual solvent composite hydrogel.
[0085] Embodiment 15
[0086] 3-Aminopropylmethyldimethoxysilane (81.6 g, 0.5 mol) and water (21.6 g, 1.2 mol) were mixed in a 500 mL three-necked flask and refluxed at 150° C. for 1 hour under N2 atmosphere. Then, the mixture was kept at 150° C. under vacuum for 1 hour to remove byproducts of methanol and water and further promote the condensation of siloxane molecules. Finally, the product was cooled to 25° C. under reduced pressure to obtain a clear viscous liquid aminopolysilane.
[0087] PVA (5.0 g) and aminopolysilane (1.875 g) were dissolved in deionized water (30 mL) in a 250 mL three-necked flask and stirred in an oil bath at 95 ° C for 1 h until the solution became clear. Continue to add PA (20 mL) and stir for 1 h until a clear mixture is obtained. The mixture was centrifuged at 4000 rpm for 10 minutes to remove bubbles and then poured into a mold. The mold was frozen at -20 ° C for 21 h and thawed at room temperature for 3 h. After repeating this process three times, a silicone-enhanced polyvinyl alcohol composite hydrogel was obtained. Finally, the obtained silicone-enhanced polyvinyl alcohol composite hydrogel was soaked in distilled water for 24 hours and replaced three times to remove any residues.
[0088] The organosilicon reinforced polyvinyl alcohol composite hydrogel was immersed in a 50% volume concentration glycerol (Gly) aqueous solution for 12 hours to obtain an organic solvent-water dual solvent composite hydrogel.
[0089] Example 16
[0090] N-(β-aminoethyl-γ-aminopropyl)methyldiethoxysilane (127.2 g, 0.5 mol) and water (21.6 g, 1.2 mol) were mixed in a 500 mL three-necked flask and refluxed at 150° C. for 1 hour under N2 atmosphere. Then, the mixture was kept at 150° C. under vacuum for 1 hour to remove byproducts of methanol and water and further promote the condensation of siloxane molecules. Finally, the product was cooled to 25° C. under reduced pressure to obtain a clear viscous liquid aminopolysilane.
[0091] PVA (5.0 g) and aminopolysilane (1.875 g) were dissolved in deionized water (30 mL) in a 250 mL three-necked flask and stirred in an oil bath at 95 ° C for 1 h until the solution became clear. Continue to add PA (20 mL) and stir for 1 h until a clear mixture is obtained. The mixture was centrifuged at 4000 rpm for 10 minutes to remove bubbles and then poured into a mold. The mold was frozen at -20 ° C for 21 h and thawed at room temperature for 3 h. After repeating this process three times, a silicone-enhanced polyvinyl alcohol composite hydrogel was obtained. Finally, the obtained silicone-enhanced polyvinyl alcohol composite hydrogel was soaked in distilled water for 24 hours and replaced three times to remove any residues.
[0092] The organosilicon reinforced polyvinyl alcohol composite hydrogel was immersed in a 50% volume concentration glycerol (Gly) aqueous solution for 12 hours to obtain an organic solvent-water dual solvent composite hydrogel.
[0093] Embodiment 17
[0094] Trimethoxy [3- (methylamino) propyl] silane (96.7g, 0.5moL) and water (21.6g, 1.2moL) were mixed in a 500mL three-necked flask and refluxed at 150°C for 1 hour under N2 atmosphere. Then, the mixture was kept at 150°C under vacuum for 1 hour to remove byproducts of methanol and water and further promote the condensation of siloxane molecules. Finally, the product was cooled to 25°C under reduced pressure to obtain a clear viscous liquid aminopolysilane.
[0095] PVA (5.0 g) and aminopolysilane (1.875 g) were dissolved in deionized water (30 mL) in a 250 mL three-necked flask and stirred in an oil bath at 95 ° C for 1 h until the solution became clear. Continue to add PA (20 mL) and stir for 1 h until a clear mixture is obtained. The mixture was centrifuged at 4000 rpm for 10 minutes to remove bubbles and then poured into a mold. The mold was frozen at -20 ° C for 21 h and thawed at room temperature for 3 h. After repeating this process three times, a silicone-enhanced polyvinyl alcohol composite hydrogel was obtained. Finally, the obtained silicone-enhanced polyvinyl alcohol composite hydrogel was soaked in distilled water for 24 hours and replaced three times to remove any residues.
[0096] The organosilicon reinforced polyvinyl alcohol composite hydrogel was immersed in a 50% volume concentration glycerol (Gly) aqueous solution for 12 hours to obtain an organic solvent-water dual solvent composite hydrogel.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an organic solvent-water dual solvent composite hydrogel, characterized in that: The following steps are involved: S1, dissolving aminopolysilane and polyvinyl alcohol in water and heating for reaction, adding polyacid for reaction to obtain a mixture, and subjecting the mixture to centrifugation and cyclic freeze-thaw to obtain an organosilicon-enhanced polyvinyl alcohol composite hydrogel; S2. placing the organosilicon-reinforced polyvinyl alcohol composite hydrogel in an organic solvent or an aqueous solution of an organic solvent for solvent replacement to obtain an organic solvent-water dual solvent composite hydrogel.
2. The preparation method according to claim 1, characterized in that In step S1, the aminopolysilane is prepared by mixing aminosilane and water, heating and refluxing, vacuum dehydration, and reduced pressure cooling.
3. The preparation method according to claim 2, characterized in that: The aminosilane includes at least one of 3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, N-(β-aminoethyl-γ-aminopropyl)methyldiethoxysilane and trimethoxy[3-(methylamino)propyl]silane, and the molar ratio of the aminosilane to water is 1:(2-5).
4. The preparation method according to claim 2, characterized in that: Heat to 140℃~160℃ in N2 atmosphere and reflux for 1~2h, remove water in vacuum at 140℃~160℃ for 1~2h, and cool to 20℃~30℃ under reduced pressure.
5. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of aminopolysilane to polyvinyl alcohol is (0.0625-0.75):1, the polyacid includes at least one of phytic acid, citric acid and tripolyphosphoric acid, and the ratio of polyvinyl alcohol, water and polyacid is (1g):(5-7mL):(3-5mL).
6. The preparation method according to claim 1, characterized in that: In step S1, the mixture is heated to 90°C to 100°C and reacted for 1 to 2 hours, and a polyacid is added and reacted for 1 to 2 hours.
7. The preparation method according to claim 1, characterized in that: In step S2, the organic solvent includes at least one of ethanol, propylene glycol and dimethyl sulfoxide, and the volume concentration of the organic solvent in the aqueous solution of the organic solvent is 0% to 100% and does not include 0% and 100%; the time for solvent replacement is 12 to 48 hours, and the number of solvent replacements is 1 to 3 times.
8. An organic solvent-water dual solvent composite hydrogel, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the organic solvent-water dual solvent composite hydrogel as claimed in claim 8 in flexible sensing.
10. A wearable strain sensor, characterized in that: It comprises the organic solvent-water dual solvent composite hydrogel as described in claim 8.
Citation Information
Patent Citations
Preparation method of high-performance polyvinyl alcohol hydrogel artificial cartilage substitute material
CN108310469A
Organic silicon-polyvinyl alcohol nano-composite hydrogel and method for preparing same
CN109456502A
High-toughness wide-temperature-range anti-swelling oil hydrogel material for wearable multi-mode sensor
CN116655960A
Starch / ionic liquid / polyvinyl alcohol high-performance composite hydrogel as well as preparation method and application thereof
CN116731459A
Polymer composition for prolonged-use soft contact lenses and a method for preparation thereof
RU2269552C1
